Effects of alkyl chain length on film morphologies and photocurrent responses of tetrathiafulvalene-bipyridinium charge-transfer salts: a study in terms of structures. Issue 16 (31st March 2016) - Huo, Peng; Xue, Li-Jun; Li, Yan-Hong; Chen, Ting; Yu, Lei; Zhu, Qin-Yu; Dai, Jie
Abstract : Viologen dication derivatives are used to assemble charge-transfer salts and films with tetrathiafulvalene-bicarboxylate to explore the relationship of alkyl chain length to molecular structures and film morphologies. Abstract : Viologen dication derivatives with a series of alkyl chains are used to assemble charge-transfer salts and films with dimethylthio-tetrathiafulvalene-bicarboxylate which aims to explore the relationship of the alkyl chain length to molecular structures and film morphologies which are important points for the design of molecular materials and manipulation of molecular devices. Four charge-transfer salts generally formulated as [(C n V)(HL)2 ] [ n = 4(1 ), 8(2 ), 12(3 ) and 16(4 )] are prepared and1–3 are characterized by single-crystal X-ray structural analysis. In the short alkyl chain compound, TTF and C4 V moieties are regularly arranged and effectively stacked with strong charge-transfer interactions. Lengthening the alkyl chain of the bipyridinium cation reduces the regular and close arrangement of the cations and anions in the crystals, which weakens the charge-transfer interaction while increasing the amphiphilic assembly of the films. Their film morphologies change from crystals to fused crystals, band-like structures and finally to smooth films with the increase of the alkyl chain length. The effects of alkyl chain length on photocurrent intensity are different between the crystal sample-modified electrodes (in the order of1 >2 >3 =4 ) and the film-modified electrodes (in the order of2 >1 =3 >4 ), because both inter-ion interactions and film-forming properties should be considered for the film electrodes. This is a systematic study of the effect of alkyl chain substitution on film morphologies in terms of crystal structures.